(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Main Problem: Robotic-assisted techniques are common for living-donor nephrectomy. While robotic stapling offers increased surgeon control, there is limited comparative data versus laparoscopic linear stapler use for ligation of renal vessels. Methods: We retrospectively reviewed 32 consecutive robotic-assisted donor nephrectomies by a single surgeon for perioperative outcomes. Results: Patients in the robotic stapler (RS; N=20) and laparoscopic stapler (LS; N=12) groups were comparable in terms of age and BMI. Estimated blood loss (p = 0.62), warm ischemia time (p=0.50), and console time (p=0.56) were similar between the RS and LS groups. There were no stapler misfires or major intraoperative complications in either group and no cases required conversion to open. Conclusions: Robotic stapler use is safe and effective in robotic-assisted donor nephrectomy. Further research on prevalence of robotic stapler use is needed to quantity the associated complication rate.